Novel Aspects of Extracellular Vesicles in the Regulation of Renal Physiological and Pathophysiological Processes - Rigalli, Juan Pablo; Barros, Eric Raul; Sommers, Vera; Bindels, René J. M.; Hoenderop, Joost G. J. (Frontiers in Cell and Developmental Biology, 2020)
Extracellular vesicles (EV) are nanosized particles released by a large variety of cells. They carry molecules such as proteins, RNA and lipids. While urinary EVs have been longer studied as a source of biomarkers for renal and non-renal disorders, research on EVs as regulatory players of renal physiological and pathological processes has experienced an outbreak recently in the past decade. In general, the microenvironment and (patho)physiological state of the donor cells affect the cargo of the EVs released, which then determines the effect of these EVs once they reach a target cell. For instance, EVs released by renal epithelial cells modulate the expression and function of water and solute transporting proteins in other cells. Also, EVs have been demonstrated to regulate renal organogenesis and blood flow. Furthermore, a dual role of EVs promoting, but also counteracting, disease has also been reported. EVs released by renal tubular cells can reach fibroblasts, monocytes, macrophages, T cells and natural killer cells, thus influencing the pathogenesis and progression of renal disorders like acute kidney injury and fibrosis, nephrolithiasis, renal transplant rejection and renal cancer, among others. On the contrary, EVs may also exert a cytoprotective role upon renal damage and promote recovery of renal function. In the current review, a systematic summary of the key studies from the past five years addressing the role of EVs in the modulation of renal physiological and pathophysiological processes is provided, highlighting open questions and discussing the potential of future research.